Clinical considerations for the evaluation of patients with left ventricular assist devices. Issue 1 (January 2022) - McMullen, Leah; Barker, Kelly; Fried, Justin; Wagener, Gebhard
ABSTRACT: A left ventricular assist device (LVAD) provides mechanical circulatory support for patients with end-stage heart failure. As these devices become more prevalent, clinicians must be familiar with the device's function, common complications, and management strategies when evaluating this patient population.